Diagnosing syntax - Cheng, Lisa Lai Shen (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Diagnosis is an essential part of scientific research. It refers to the process of identifying a phenomenon, property, or condition on the basis of certain signs and by the use of various diagnostic procedures. This book is the first ever to consider the use of diagnostics in syntactic research and focuses on the five core domains of natural language syntax - ellipsis, agreement, anaphora, phrasal movement, and head movement. Each empirical domain is considered in turn from the perspectives of syntax, syntax at the interfaces, neuropsycholinguistics, and language diversity. Drawing on the expertise of 20 leading scholars and their empirically rich data, the book presents current thoughts on, and practical answers to, the question: What are the diagnostic signs, techniques and procedures that can be used to analyse natural language syntax? It will interest linguists, including formalists, typologists, psycholinguists and neurolinguists